FACTORS AFFECTING SECOND AND THIRD TRIMESTER PREGNANT WOMEN’S READINESS FOR DELIVERY AT PMB SHINTA MEDAN JOHOR DISTRICT IN MEDAN CITY, NORTH SUMATRA PROVINCE IN 2025 - Marta Armita Silaban; Ernamari; Eva Dona Sinaga; Novita Andriani Br Manjorang; Damayanty S; Sri Nengsih Sihombing (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
One of reason height number death mother (AKB) and figures death baby (AKB) is unpreparedness Mother pregnant in face her delivery . This is can happen consequence delay handling moment happen complications childbirth in mothers . Readiness Mother in face labor can prevent occurrence complications in mother and baby with notice factor risks to the mother​ during the pregnancy process . There is readiness labor can done with prepare plan birth and preparation plan If occurs during labor mother . Purpose study This is identify and analyze factor affecting​ Mother pregnant in the second and third trimesters of pregnancy readiness childbirth . Sort of research This is a cross-sectional design and is quantitative and survey analytical. The study sample 32 women in their second and third trimesters who are moms were selected using purposive sampling. The inquiry This was put into practice in 2025 in PMB Shinta Medan City in the province of North Sumatra. Instrument studies employ questionnaires and apply the chi-squared statistical test to analyze data. According to the study’s findings, 18 moms, or 56.3% of the total number of deliveries at PMB Shinta, are not prepared.There is significant relationship​ between knowledge mother ( p. value 0.047<0.05), parity Mother with p. value 0.029<0.05) and exposed information ( p. value 0.016<0.05). The conclusion is expected in mothers pregnant especially TM II and III so that they can prepare her delivery use prevent occurrence risk complications. Recommended for officer health can give Mother education health and motivation Mother pregnant in readiness mother during childbirth . Keywords: Pregnant Women, Readiness , Childbirth , Parity, Knowledge